Leadership enhancing the lessons of experience - Hughes, Richard L.; Ginnett, Robert C.; Curphy, Gordon J. (McGraw-Hill Education, 2015)
Consists of 16 chapters, four of which cover specific leadership skills and qualities. This book draws upon three different types of literature - empirical studies; interesting anecdotes, stories and findings; and leadership skills - to create a text that is personally relevant, interesting, and scholarly